2016
DOI: 10.1007/s10334-016-0535-6
|View full text |Cite
|
Sign up to set email alerts
|

Volume measurements of individual muscles in human quadriceps femoris using atlas-based segmentation approaches

Abstract: In the present study, we demonstrated that both multi-atlas and single-atlas approaches were relevant for the segmentation of individual muscles of the QF in healthy subjects. Considering muscle volume measurements, the single-atlas method provided promising perspectives regarding longitudinal quantification of individual muscle volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 37 publications
0
77
0
Order By: Relevance
“…Landmarks‐based 3‐D warp deformation fields were used to impose strong constraints in order to increase the accuracy of the previous reported method (Le Troter et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Landmarks‐based 3‐D warp deformation fields were used to impose strong constraints in order to increase the accuracy of the previous reported method (Le Troter et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…We mainly showed that with the initial input of only two manually segmented slices, the automated segmentation of the QF muscles was accurate on a large part of the thigh. According to the metrics reported in Table 1, our method provided better results as compared to the full multi-atlas based automatic approach Le Troter et al initially proposed for the same muscle group [7] with average DSC values ranging from 0.72 to 0.94. We expect an even better accuracy of our method using a larger amount of manually-segmented slices as initial input.…”
Section: Qualitative and Quantitative Validationmentioning
confidence: 99%
“…Sdika et al [6] recently demonstrated the reliability of a multi-atlas segmentation approach for the automatic segmentation and volume quantification of individual leg muscles in rat. Le Troter et al [7] evaluated the potential of this approach for quantification of individual muscle volume and reported the corresponding utilization for longitudinal studies in human. They illustrated that a fully-automated method was appropriate for large muscle groups but not for individual muscles and proposed a single-atlas based method as an alternative solution.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that there are significant progresses made in automatic segmentation of muscles from MR images [5,11,13,15,17–19,22,28,30], only a few methods have been introduced before to address the problem of automatic segmentation of muscles from CT data [9,10,12,20,20,29]. The published CT muscle segmentation methods can be classified into two categories: 2D methods and 3D methods.…”
Section: Introductionmentioning
confidence: 99%